Pearlmillet Yield Prediction Models For Kutch Region oflndia, Using Climatic Water Balance Parameters - Singh, R S; Ramakrishna, Y S (Annals of Arid Zone, 2016)
Three parameters viz; actual evapotranspiration (A E) during the total crop growing period, during the reproductive phase alone and also the Index of Moisture Adequacy (AE/PE) during reproductive phase have been worked out in respect of pearlmillet crop grown in Kutch region, for the period 1970 to 1988. Using the data for period 1970-84, various regression models were developed to predict and estimate the production of pearlmillet in the arid Kutch district of India. Among all the models, the reciprocal hyperbola curves gave the best fit and explained a maximum of 80% variation in pearlmillet yield. Performance of the models is also tested with data of later years. 1985-88. The suitability of these models for pearlmillet yield prediction has been discussed.